1ISG-013 Economic impact of orphan drugs used in paediatric patients attending hospital outpatient pharmacy and day hospital. (2nd March 2018) - Martinez, C Alonso; Fernández-Polo, A; Jiménez-Lozano, I; Garau, M; Cabañas, MJ; Cañete, C; García-Palop, B; Larrosa-García, M; Betriu, L; Serramontmany, E; Alerany, C
Abstract : Background: Orphan drugs (ODs) are designed to treat rare diseases (RD), which are those affecting a small number of people (prevalence <1/2000 inhabitants). Purpose: To assess the economic impact of drugs used to treat RD in a hospital outpatient paediatric pharmacy (HOPP) and a paediatric day hospital (PDH). Material and methods: Observational, retrospective, transversal study conducted at a third-level maternal and child University Hospital during 2016. All paediatric patients(<18 years' old) were included, as well as adults with cystic fibrosis. Chemotherapy treatments administered in the Oncology Day Hospital were excluded. Pharmaceutical drug, active ingredient, number of packages, real unit cost, consumption data, medical service and treating unit were collected from pharmacy-dispensing software(Silicon ® ) The Orphanet ® database was used to classify the drugs in ODs (recognised as orphan by the European Union or abroad) or drugs without orphan designation. Results: Four hundred and ten drugs were identified to treat RD and 51 (12.4%) were ODs: 42 were dispensed in the HOPP and nine were administered in the PDH. There were 2442 patients who received at least one drug to treat RD: 2044 from the HOPP and 562 from the PDH (164 patients received treatment in both settings) Of all patients, 441 (18.1%) received at least one OD: 420 (20.5%) in the HOPP and 23 (4.1%) in the PDH (two patients in both). Drugs used to treat RDs accounted for €7.7 million: €3.8 million in the HOPP and €3.9 million in the PDH. OD cost represented 36.3% of the total pharmaceutical expenditure in drugs at the HOPP and 71% at the PDH. Bosentan, adalimumab, ivacaftor, ataluren and sildenafil were the five drugs with the greatest economic impact in the HOP budget and eculizumab, idursulfase, elosulfase, galsulfase and velaglucerase in the PDH budget. Conclusion: Pharmacological treatment with ODs has a great impact on direct medical costs, involving more than 50% of total pharmaceutical expenditure. Although it is more common in the outpatient pharmacy than in the day hospital (20.5% and 4.1% of the assisted patients, respectively), the OD cost reaches 71% of the expenditure on drugs in the PDH setting. The HOPP and the PDH need to develop strategies focusing on ODs, but also on treatments in special situations and extemporaneous drug formulations used to treat patients affected by RD. References and/or Acknowledgements: Thanks to all authors for their involvement No conflict of interest